Diagnostic System of Power Oil Transformer in Accordance with Thermal Parameters - D. I. Zalizny; O. G. Shirokov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a device and algorithms for early detection of slowly developing faults in a power transformer that cause its abnormal heating. The device differentiates from the others that it requires only temperature measurement of  transformer tank surface and ambient temperatures. Experimental 63 MV×A autotransformer tests have proved faithfulness of the developed algorithms.